Improved osteogenic differentiation of human amniotic mesenchymal stem cells on gradient nanostructured Ti surface. Issue 9 (17th June 2020) - Wang, Wei; Wang, Zhenbo; Fu, Yating; Dunne, Nicholas; Liang, Chen; Luo, Xue; Liu, Keda; Li, Xiaoming; Pang, Xining; Lu, Ke
Abstract: Titanium (Ti) and Ti‐based alloys are widely used in the manufacture of dental and orthopedic implants. However, how to improve their osteogenic differentiation ability is still a key issue to be resolved. In this study, gradient nanostructured surface (GNS) samples were prepared by surface mechanical grinding treatment, and coarse‐grained (CG) samples were obtained by recrystallization annealing, making sure that the two kinds of specimens had similar roughness. Then, human amniotic mesenchymal stem cells (hAMSCs) were cocultured with the two kinds of Ti to investigate the material effects on the cellular functions. The results demonstrated that the grains with size 56 nm were formed on the surface of the GNS Ti, and the grain size gradually increases from the sample surface to interior. Compared to the CG samples, the GNS ones could make the adhesion effect of the hAMSCs better, and promote the cell proliferation and osteogenic differentiation more significantly, the preliminary mechanism of which might be due to their specific nanostructure, the thicker oxide layer formed on their surface and the enhanced hardness. Our results indicated that the gradient nanostructured Ti materials could enhance both osteogenic differentiation and mechanical properties, which may possess broader applications in bone tissue engineering and clinical implanting.